Frankie's New York Adventure - Lampard, Frank (Little, Brown Book Group London, 2015)
Frankie and his team love playing football. There's always time for a game. And now that they have their magical football they're playing against teams they never imagined! During a PE game with a difference, Frankie and his friends are transported to meet a giant, green woman - the Statue of Liberty! They also meet an American boy whose ambition of baseball victory is about to be dashed. Can they race through New York in time to help someone's sporting dream come true?